Adjectives and their Attributives and Predicative Variations (Journal of Namibian Studies : History Politics Culture, 2023)
It has been difficult for adjectives to be identified as a lexical category. This paper examines adjectives (attributively and predicatively) to locate points of challenge and difficulty. By employing a theoretical analysis depending on a number of previous studies. This procedure is applied to examine such studies. Perceptions about the aforementioned types of adjectives are carried out to ensure that sample of the study correspond to the aim of the study itself. However, other adjectives can have a solo function either as an attributives or predicatives. In this paper, an identification as well as a differentiation of adjectives as a lexical category is to be shown. However, this paper argues that the semantic treatment of attributive adjectives can denote to second-order identity-typed functions. This has a conceptual merit for a theory assuming that attributive adjectives signify properties. It is shown that the merits of analyzing the attributive adjectives as second-order identity-typed functions captivating nominal arguments. Moreover, it is apparent that both types function as properties of a type-shifting operator to derive the attributive use of adjectives from the predicative use.